2020
DOI: 10.1121/10.0001569
|View full text |Cite
|
Sign up to set email alerts
|

Masking of short tones in noise: Evidence for envelope-based, rather than energy-based detection

Abstract: The “temporal effect” in simultaneous masking may be characterized by better probe detection thresholds for a short, tonal probe presented at the temporal center of a masker compared to at the onset of a masker. Energy-based models of masking have been used to interpret the temporal effect as evidence that the gain of the auditory system decreases during acoustic stimulation. This study shows that masking from temporal-envelope fluctuations of a precursor or from a temporal gap between stimuli violates the ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Energetic masking describes the loss of target information due to the spectro-temporal overlap with the masker. Envelope masking describes the deleterious effects of envelope interference even when the spectral overlap between target and masker is reduced (e.g., Fogerty et al , 2016 ; Stone and Canavan, 2016 ; Jennings and Chen, 2020 ). Informational masking in the context of this study is restricted to lexical interference (i.e., both the target and masker speech are intelligible) and talker characteristics (e.g., talker sex, the number of maskers).…”
Section: Introductionmentioning
confidence: 99%
“…Energetic masking describes the loss of target information due to the spectro-temporal overlap with the masker. Envelope masking describes the deleterious effects of envelope interference even when the spectral overlap between target and masker is reduced (e.g., Fogerty et al , 2016 ; Stone and Canavan, 2016 ; Jennings and Chen, 2020 ). Informational masking in the context of this study is restricted to lexical interference (i.e., both the target and masker speech are intelligible) and talker characteristics (e.g., talker sex, the number of maskers).…”
Section: Introductionmentioning
confidence: 99%
“…Steady noise largely produces energetic masking at the periphery (i.e., spectral overlap between the target and masker). Modulated noise and multi-talker babble may produce energetic as well as envelope masking in cochlear regions remote from the target, and may not depend on the degree of spectral overlap between the target and the masker 28 . Competing speech may produce energetic, envelope, and informational masking (due to lexical interference, talker characteristics, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Informational masking is not caused by physical interactions between the target and masker and/or overlap at the auditory periphery ( Kidd & Colburn, 2017 ). Envelope masking reflects interference between target and masker temporal envelopes, even when spectral overlap (energetic masking) is reduced (e.g., Bronkhorst, 2015 ; Conroy & Kidd, 2021 ; Conroy et al, 2023 ; Fogerty et al, 2016 ; Jennings & Chen, 2020 ; Stone & Canavan, 2016 ). Conroy and Kidd (2021) found that uncertainty regarding masker modulation frequency could have adversely affected the detection of target modulations.…”
Section: Introductionmentioning
confidence: 99%